Model of care risk factors associated with tuberculosis in children - Sri Umijati; Susilowati Andajani (AcTion: Aceh Nutrition Journal, 2024)
Mothers play an important role in reducing the risk factors for parenting related to the increased incidence of childhood tuberculosis (TB). This risk factors are very complex and need to be simplified in a model. The purpose of the study to determine the model of risk factors for parenting related to childhood TB. This cross-sectional study was conducted in 2014 in the Tambak Sari, Simokerto, and Kenjeran Districts, Surabaya city, Indonesia. A total of 39 mothers (total sample) whose family members had TB were interviewed about care related to the incidence of sick children. Their children's nutritional status was assessed. Furthermore, a simultaneous path analysis was conducted to determine the model. Result, the model of risk factors for caring for children with TB was appropriate (x2=6,02, df=10, p=0,8), as was the model of risk factors for caring for children with TB and other infections (x2=7,68, df=10, p=0,66). TB in children was influenced by their nutritional status (β=0,42). Children's nutritional status can be improved by improving mothers’ ability to care for sick children (in both models, β=0,16). In conclusion, the ability to care for sick children forms a model for determining the incidence of TB in children through their nutritional status.